The Influence of Prior Obstetrical History on Current 17-Hydroxyprogesterone Caproate Use - Carla E. Ransom; Jeanette R. Chin; Hilary A. Roeder; Tammy R. Sinclair; R. Phillips Heine; Amy P. Murtha (Journal of Pregnancy)
Objective. To determine if gestational age of prior preterm delivery influences a woman's receipt of 17-hydroxyprogesterone caproate (17-OHP-C). Methods. Retrospective cohort of women eligible for 17-OHP-C at Duke Obstetrics Clinic were identified by medical record review. Sociodemographic and clinical characteristics were abstracted. Results. Of 104 eligible subjects, 82 (78.8%) were offered 17-OHP-C. Of these, thirty-four (41.5%) declined. The median gestational age of the most recent preterm delivery was significantly lower among subjects who accepted 17-OHP-C as compared to those who declined (28.7 vs. 34.0 weeks, 𝑃=.02) and in subjects offered 17-OHP-C compared to those not offered 17-OHP-C (30.2 vs. 36.0 weeks, 𝑃=.03). Subjects not offered 17-OHP-C were more likely to have had an interval term delivery (31.8% vs. 9.7%, 𝑃=.009) Conclusion. Women with earlier preterm deliveries were more likely to be offered and accept 17-OHP-C. Prior obstetric history may influence both providers' and patients' willingness to discuss and/or accept 17-OHP-C.